2012
DOI: 10.1097/iae.0b013e318242b965
|View full text |Cite
|
Sign up to set email alerts
|

EPIRETINAL MEMBRANE AFTER PARS PLANA VITRECTOMY FOR PRIMARY PSEUDOPHAKIC OR APHAKIC RHEGMATOGENOUS RETINAL DETACHMENTIncidence and outcomes

Abstract: The incidence of ERM after pars plana vitrectomy alone for the repair of primary pseudophakic or aphakic rhegmatogenous retinal detachment was similar to reported incidences after scleral buckling. Best-corrected visual acuity improved after surgical removal of ERM, although eyes with the macula detached had lower final BCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 11 publications
4
43
2
1
Order By: Relevance
“…Martinez-Castillo et al 15 reported ERM in 10% of the PVR eyes. This was different from our prevalence because this study was dependent on a fundus examination for detection of ERM and used OCT only to confirm clinical diagnosis of ERM.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez-Castillo et al 15 reported ERM in 10% of the PVR eyes. This was different from our prevalence because this study was dependent on a fundus examination for detection of ERM and used OCT only to confirm clinical diagnosis of ERM.…”
Section: Discussionmentioning
confidence: 99%
“…4,[9][10][11][12] Typically, a remove-and-replace approach is used when such cases undergo further attempts at surgical repair, or the SO is removed at the time of EMM removal. 4,[9][10][11][12] Typically, a remove-and-replace approach is used when such cases undergo further attempts at surgical repair, or the SO is removed at the time of EMM removal.…”
mentioning
confidence: 99%
“…Thus, it is possible that the MHs might have been developed after continuous traction caused by the ERMs. On the other hand, the risk factors for the development of ERM after the repair of rRDs include equatorial rather than anterior breaks [ 13 ] and multiple or large retinal breaks [ 14 ]. Therefore, an equatorial break could shorten the interval of MH formation after vitrectomy for rRD.…”
Section: Discussionmentioning
confidence: 99%